Advantages of targeting B cell receptor complex to treat B-cell derived autoimmune diseases and lymphomas. (August 2017) - Adem, Jemal; Eray, Mine; Eeva, Jonna; Nuutinen, Ulla; Pelkonen, Jukka
Abstract: Antibodies produced by B-cells provide protection from infectious agents. However, impaired cell death signaling pathways in B-cells can lead to cancer, immunodeficiency or autoimmune diseases. B-cell signaling molecules such as CD20, CD19, Btk, and BAFF-R are targeted by therapeutic drugs and used to treat B-cell derived lymphomas or autoimmune diseases. Nevertheless, B-cells could develop resistance to these therapeutic drugs or the therapeutic drugs may have off-target effects. For instance, repeated rituximab (anti-CD20 antibody) treatment may lead to the loss of its target cell surface molecule, CD20. In addition, in B-cell malignancies, loss of CD19 expression has been observed. Another target molecule, Btk is expressed not only in B-cells but also in mast cells, macrophages, and dendritic cells. Thus, targeting Btk could negatively regulate the functions of innate immunity. The expression of BAFF-R is thought to be restricted to B-cells but it is also expressed on T-cells. Targeting BAFF-R, therefore, may lead to depletion of T-cells in addition to B-cells. B cell receptor (BCR) expression and signaling, however, are critically important for development, differentiation and survival of B-cells. Moreover, BCR is exclusively expressed on B-cells, which makes it an excellent target to avoid off-target effects.